Expression of vascular endothelial growth factor and hypoxia-inducible factor in the airway of asthmatic patients - Lee, Sook Young; Kwon, Soon; Kim, Kwan Hyoung; Moon, Hwa Sik; Song, Jung Sup; Park, Sung Hak; Kim, Young Kyoon (Annals of allergy, asthma, & immunology, 2006)
Vascular endothelial growth factor (VEGF) is a potent proangiogenic cytokine, and it also increases vascular permeability. It is well known that VEGF levels are increased in the airway of asthmatic patients. Hypoxia-inducible factor (HIF) induces a rapid and strong increase in VEGF expression. To evaluate the relationship between VEGF level and clinical characteristics and to determine whether VEGF expression is associated with HIF expression in asthmatic patients. Bronchoscopy was performed on 30 asthmatic patients and 14 control subjects. The concentration of VEGF in the bronchoalveolar lavage fluid (BALF) was examined using enzyme-linked immunosorbent assay. We measured VEGF, HIF-1alpha, and HIF-2alpha expression on biopsy specimens by means of immunoreactivity. The VEGF level in the BALF was significantly higher in asthmatic patients than in controls. The VEGF level correlated with eosinophil counts in the BALF in asthmatic subjects (r = 0.501; P < .01). However, the VEGF level did not correlate with percentage of forced expiratory volume in 1 second and airway hyperresponsiveness. Asthmatic patients exhibited higher VEGF, HIF-1alpha, and HIF-2alpha immunoreactivity in the submucosa than did controls. Furthermore, VEGF expression correlated significantly with HIF-1alpha (r = 0.614; P = .02) and HIF-2alpha (r = 0.881; P = .001) expression. These findings suggest that VEGF may play an important role in inflammation and that VEGF level is related to HIF in bronchial asthma.